2020
DOI: 10.1093/cid/ciaa1151
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctival Scarring, Corneal Pannus, and Herbert’s Pits in Adolescent Children in Trachoma-endemic Populations of the Solomon Islands and Vanuatu

Abstract: Background In the Solomon Islands and Vanuatu, the sign trachomatous inflammation—follicular (TF) is common, but ocular infection with Chlamydia trachomatis is not. It is therefore debatable whether azithromycin mass drug administration (MDA), the recommended antibiotic treatment strategy for trachoma’s elimination as a public health problem, is necessary in this setting. We set out to estimate what proportion of adolescents were at risk of progression of trachomatous scarring. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…In communities in Guinea Bissau and Taiwan in which trachoma is endemic, 60-80% of people with TF and 20-40% of those without active trachoma have Herbert's pits or pannus. 15,22,23 Finally, only one 5-9-year-old child had clinical signs consistent with TI. In communities where trachoma is endemic, TI is frequently encountered in young children; in the long term, it is the best predictor of trachomatous scarring in adults.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In communities in Guinea Bissau and Taiwan in which trachoma is endemic, 60-80% of people with TF and 20-40% of those without active trachoma have Herbert's pits or pannus. 15,22,23 Finally, only one 5-9-year-old child had clinical signs consistent with TI. In communities where trachoma is endemic, TI is frequently encountered in young children; in the long term, it is the best predictor of trachomatous scarring in adults.…”
Section: Discussionmentioning
confidence: 98%
“…[9][10][11][12][13] As the predictive value of simple clinical assessment declines, other tools may be more useful for estimating trachoma prevalence, including assessment of conjunctival scarring and anti-Pgp3 seropositivity, each recognised as persistent markers of previous active trachoma and C. trachomatis infection. 14,15 We have previously reported that simplified grading caused overestimation of the prevalence of trachoma in a Torres Strait Island community. 9 We have therefore supplemented data from surveys in northwest Queensland recommended by the National Trachoma Surveillance and Control Reference Group by collecting additional information to determine whether community-wide treatment and further screening rounds are required.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The retrospective nature of our work increases the risk of misclassification bias. Although the patients we included had features of cicatricial trachoma, including Herbert's pits, 21 and an absence of any other obvious cause for corneal scarring, trachoma cannot be proven to be the cause of their corneal opacification or their amyloidosis.…”
Section: Discussionmentioning
confidence: 99%
“…13 Vanuatu has recently become the fourteenth country to eliminate trachoma as a public health problem; 14 its case for validation relied in part on the TF found in children's eyelids not being associated with PCR evidence of C. trachomatis infection, high levels of anti-C. trachomatis antibodies in children, or much conjunctival scarring in adolescents. 15,16 As Lynch and colleagues advise for Australia, international guidance for trachoma programs should be re-assessed.…”
mentioning
confidence: 99%